EUROPEAN ANTIQUITY IN VERBAL EXPRESSION: PHILOSOPHICAL AND CULTURAL ASPECT - Nikolaevna Kurbakova, Svetlana; Yurievna Starodubova, Olga; Igorevna Khristoforova, Natalya; Beisenovna Sabekia, Raushana; Beisenovna Askarova, Gulnara (Revista Inclusiones, 2020)
The present article deals with solving one of the fundamental problems that arise in the study of the theoretical foundations of building a cultural picture of the world, whose denotation consists of a group of natural objects. The target of analysis is the ancient Roman linguistic picture of the world, which has been verbalized in the Latin natural vocabulary. The research subject is the names of evergreen trees as the structure of a certain conceptual fragment of the world picture, which is reflected in the works of ancient Roman authors on natural topics. The article presents a reconstruction of an element of the ancient picture of the world based on the material of Latin nouns, dendrological names of evergreen trees. The analysis of the vocabulary of the works of Latin authors on natural science topics allowed determining the specifics of the linguistic picture of the world, corresponding to the ideas of the ancient Romans about the surrounding nature.